2021
DOI: 10.1016/j.celrep.2021.109173
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of B cell repertoires and emergence of cross-reactive responses in patients with different severities of COVID-19

Abstract: Patients with COVID-19 show varying severity of the disease ranging from asymptomatic to requiring intensive care. Although SARS-CoV-2-specific monoclonal antibodies have been identified, we still lack an understanding of the overall landscape of B-cell receptor (BCR) repertoires in patients with COVID-19. We use high-throughput sequencing of bulk and plasma B-cells collected over multiple time points during infection to characterize signatures of the B-cell response to SARS-CoV-2 in 19 patients. Using princip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 77 publications
4
43
0
Order By: Relevance
“…While asymptomatic COVID-19 patients displayed more abundant TCR diversity, on the contrary, they showed less BCR clonal expansion compared to moderate and severe patients. which is in line with the previous studies 28 , 40 , 41 and are likely to be associated with antibody-secreting B cells that produce antibodies to neutralize the infecting pathogen. 41 , 42 We found that patients with different conditions shared a common IGLV1/2 and IGLJ2/3 usage pattern and IGHV3 and IGHJ4 usage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While asymptomatic COVID-19 patients displayed more abundant TCR diversity, on the contrary, they showed less BCR clonal expansion compared to moderate and severe patients. which is in line with the previous studies 28 , 40 , 41 and are likely to be associated with antibody-secreting B cells that produce antibodies to neutralize the infecting pathogen. 41 , 42 We found that patients with different conditions shared a common IGLV1/2 and IGLJ2/3 usage pattern and IGHV3 and IGHJ4 usage.…”
Section: Discussionsupporting
confidence: 92%
“…which is in line with the previous studies 28 , 40 , 41 and are likely to be associated with antibody-secreting B cells that produce antibodies to neutralize the infecting pathogen. 41 , 42 We found that patients with different conditions shared a common IGLV1/2 and IGLJ2/3 usage pattern and IGHV3 and IGHJ4 usage. Moreover, we found a higher proportion of IGHV3 and IGHJ4 usage in asymptomatic patients.…”
Section: Discussionsupporting
confidence: 92%
“…Convergent lenient VH-only clonotypes have been identified between multiple SARS-CoV-2 infected or convalescent individuals [ 12 18 ] and across different studies, for example the overlap between the clonotypes found by Galson et al . [ 4 ] and Nielsen et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, the usage of the IGHV3-7 gene increased after Hepatitis B vaccination [42]. Also, the abundance of the IGHV4-59, IGHV4-39, IGHV3-23, IGHV3-53, IGH3-66, IGHV2-5, and IGHV2-70 genes was found in SARS-CoV2 infection studies [43][44][45][46]. Similarly, we observed an increased usage of the IGHV3-23 gene on all visits post-vaccination; the usage of the IGHV1-2, IGHV1-18, IGHV3-33, IGHV4-39, IGHV4-31 genes increased at d5, d7 and d10 post-vaccination; and IGHV5-51 was highly used at d10 post-vaccination.…”
Section: Discussionmentioning
confidence: 93%